A comparative study of the gas sensing properties of hierarchical ZnO nanostructures. Issue 7 (16th March 2016) - Capochichi‐Gnambodoe, Martine; Habba, Yamina Ghozlane; Leprince‐Wang, Yamin
Abstract: Two types of ZnO nanostructure have been fabricated to make a comparative study on their gas sensing performance: the conventional ZnO nanowire arrays were synthesized by hydrothermal method and the hierarchical ZnO nanowires/nanofibers nanostructures were prepared through a combination of the hydrothermal and electrospinning methods. Field emission scanning electron microscopy study showed a quiet homogeneous morphology both for both nanostructures. Three kinds of commonly used gases, such as ethanol, acetone and ammonia were chosen for ZnO nanostructure gas sensing property study. The UV‐Visible spectroscopy measurements showed a higher detection sensitivity of ZnO NWs for ammonia compared to ethanol and acetone, and an enhanced sensing performance for the hierarchical nano‐ structure, which has a higher surface to volume ratio. On the other hand, the enhancement was more obviously in the case of ethanol sensing. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)